PWE-094 Understanding non-participation in bowel cancer screening: a qualitative study. (28th May 2012) - Hall, N J; Rubin, G P; Weller, D; Wardle, J; Dobson, C; Ritchie, M; Rees, C
Abstract : Introduction: Uptake of the national bowel cancer screening programme (BCSP), at 52%, needs to be improved or at least maintained if the screening programme is to achieve projected reductions in mortality and morbidity. Understanding the origins of non-participation is therefore important. This study used qualitative methods to explore the beliefs and experiences of individuals who had not responded either to their screening invitation or reminder. Methods: In-depth qualitative interviews with volunteers were used to enable maximum opportunity for exploration and inductive hypothesis generation. Non-participation was defined as having refused all of the invitations and reminders for FOB test screening received from the North East Hub of the BCSP at the time of contact. Interviewees were purposefully sampled to allow for diversity in terms of gender, geographical location and socio-economic status. Data collection and analysis were carried out using strategies consistent with the principles of grounded theory with an emphasis on the constant comparison method. Data collection and analysis took place concurrently and continued until saturation (27 interviews). Results: The interviews provided an in-depth understanding of a range of reasons and circumstances surrounding non-participation, including contextual and environmental influences as well as factors specific to the screening test. The nature of the data also allowed an appreciation of the potential for changes in beliefs, awareness and intention over time. Most of the interviewees had positive attitudes towards the BCSP, even those who did not feel screening was appropriate for them or who did not wish to take part. Many had intended to take part or intended to take part in the future. The main emergent categories included: practicalities of screening, value of screening, knowledge and awareness, risk perceptions, intention, embarrassment, good "citizenship", guilt, control, and the influence of others. Conclusion: A range of different approaches may be required to improve uptake, depending on the experiences, circumstances, beliefs and existing levels of intention of non-participants. Many of the interviewees in this study reported an intention to take part in future screening rounds. This group might be responsive to repeat invitations, reminders, and aids to making the test practical. Individuals who are opposed to screening (or BCS in particular) may have been less willing to be interviewed. Research is needed to ascertain whether different groups of non-responders require different approaches to intervention. Competing interests: None declared.